(untitled) (Research, Society and Development, 2021)
Objective: To compare and analyze the effectiveness of exercise and supplemental diet in the treatment of sarcopenic obesity. Method: Integrative literature review based on articles published in journals indexed in the following databases: Virtual Health Library (VHL) and US National Library of Medicine - National Institutes of Health (PubMed). With the help of Health Sciences Descriptors (DeCS) the keywords were selected: Obesity, Sarcopenia, Exercise and Dietary. Results: After analyzing the articles, it was found that 66.67% of these stated that the combination of physical exercise and a supplemental diet resulted in good efficacy in the treatment of sarcopenic obesity, 11.11% observed that the isolated practice of physical exercise, especially strength, has an effective result, 11.11% evaluated only protein supplementation and then observed effective results and 11.11% identified that the benefits of isolated physical activity were the same as those obtained through combination of physical activity and use of a high-protein diet. Conclusion: According to the studies evaluated, the practice of physical exercise coupled with a high-protein diet culminates in an effective treatment for sarcopenic obesity. However, more accurate studies are needed to determine a clinical approach that composes an adequate protocol for the problem in question.